An epoch-making document. In commemoration of the second anniversary of the publication of the circular. Publ. on May 17, 1968, by the Editorial departments of "Renmin Ribao", "Hongqi" and "Jiefangjun Bao" (N.pl., 1968)
Reprinted by "China Reconstructs", July 1968.